Transformasi guru dalam pengajaran dan pembelajaran mengenai kemahiran membuat hipotesis dalam kalangan murid sekolah rendah - Darus, Faridah; Saat, Rohaida Mohd; Zakaria, Abd Razak (Faculty of Education, University of Malaya, 2013)

(untitled)
Science process skills are important in the teaching and learning of science starting with basic science process skills, followed by integrated process skills. Hypothesis making skills are one of the integrated science process skills. This study was conducted to examine the mastery level of hypothesis making skills among primary school children. Qualitative approach was used by using the data collection method through observation, interviews and documents analysis which involved six students as participants and an elementary school teacher together with three high school teachers. Data analysis using the N-Vivo 8 produced five themes, namely (a) the dominance of the variable concepts, (b) the capability to indicate the relationship between variables, (c) the ability to stating hypotheses, (d) the mastery of hypothesis concept and (e) capability to relate hypothesis with hypothesis testing experiment. Students' mastery level in hypothesis making skills was at low and depended on the mastery of previous science process skills. Improvement of teaching skills and practices needed in the transformation of teaching and learning to improve the mastery of hypothesis making skills. Inquiry approach, emphasis on existing knowledge, students ‘cognitive ability as well as learning experiences that are meaningful to them and not emphasize on exercise and memorizing methods should be practiced by teachers. Five elements in the transformation of teaching for quality learning that should be practiced by teachers are: (a) the implementation of effective hands-on and minds on activities, (b) implementation of concepts and skills, (c) coaching skills, (d) micro thinking, and (e) reflections mastery and students’ perspective. In the transformation of teaching practices can help students in mastering hypothesis making skills and can be developed when they pursue science education at the next level.